Re: A case of acute renal failure requiring emergency hemodialysis due to hypothermia-associated rhabdomyolysis - Özdemir, Serdar (Journal of Surgery and Medicine, 2022)
We have read the article titled “A case of acute renal failure requiring emergency hemodialysis due to hypothermia-associated rhabdomyolysis” published by Vural et al. with great interest. Acute renal failure is an uncommon diagnosis in patients presenting to the emergency department, and rhabdomyolysis is a relatively rare cause. The etiologic factors for rhabdomyolysis may be classified as hereditary and acquired (traumatic, and non-traumatic) causes. We thank the authors for this informative and successful case presentation. In this letter we also would like to mention a few important points and present an interesting phenomenon that we encountered.